2014
DOI: 10.1177/039463201402700210
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting Quality of Life in a Group of Italian Children with Asthma

Abstract: The measure of Quality of Life (QoL) has become one of the most important criteria used to assess the impact of chronic illness, such as asthma, on the patient's daily life, in adults and children alike. The objective of our open observational study was to measure the QoL and analyze several factors that potentially affect QoL, such as symptoms and functional respiratory parameters, in a cohort of children with asthma. One hundred and twenty-seven children with asthma, 6 to 14 years of age, living in the city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this study, young age group of patients adversely affected physical domain score being worse in asthmatic children than asthmatic adolescents; this study revealed that there were higher scores of overall and individual QOL domains among asthmatic adolescents than asthmatic children, both total and single domain scores improve as the age of children increases. [24,25] Adolescents are able to handle the burden of the disease than younger children owing to cognitive and emotional developmental variations in grasping the content measured.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, young age group of patients adversely affected physical domain score being worse in asthmatic children than asthmatic adolescents; this study revealed that there were higher scores of overall and individual QOL domains among asthmatic adolescents than asthmatic children, both total and single domain scores improve as the age of children increases. [24,25] Adolescents are able to handle the burden of the disease than younger children owing to cognitive and emotional developmental variations in grasping the content measured.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gender and income were the independent factors that affected the QOL levels. Indinnimeo et al 16 found that female patients were more likely to have poor QOL than male patients. The results were confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Indinnimeo et al 16 found that female patients were more likely to have poor QOL than male patients. The results were confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has investigated factors associated with quality of life in patients with asthma and approaches to improve quality of life. Clinical studies have shown that lung function, number of asthma symptoms, level of asthma control and obesity influence asthma quality of life (6)(7)(8)(9)(10). Low coping and problem solving skills and depression have also been associated with worse quality of life in patients with asthma (11,12).…”
Section: Introductionmentioning
confidence: 99%